Mapping Research in Teacher Education on Diversities and Inequalities: Opening Possibilities Through Social Cartography - Jeannie Kerr; Vanessa Andreotti (Journal of Contemporary Issues in Education, 2020)
This article considers the potential of the methodology of social cartography to open generative possibilities in research on diversities and inequalities in teacher education in the international context. Research in teacher education focusing on difference or diversities and inequalities offers highly diverse practices and orientations, yet we have found that intelligibility across research communities can be challenging and ultimately limiting for the field. Social cartography is a methodology that attempts to address this issue, inviting researchers and practitioners to create forms of conversation that are more tentative, self-critical, and generative. In this article, we introduce our priorities in teacher education that center awareness of social-cultural commitments and assumptions, as well as historical context. We then share a social cartography of teacher education research we have created to reveal the possibilities of social cartography for teacher education, as well as an invitation to open needed dialogue amongst teacher education researchers and practitioners.